2019
DOI: 10.1021/acsami.8b22297
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Fluorescence Properties of Nanoemulsions for Single Particle Tracking in Live Cells

Abstract: Nano-emulsions (NEs) are biocompatible lipid nanoparticles composed of an oily core stabilized by a surfactant shell. It is acknowledged that the surface decoration with poly(ethylene glycol) (PEG), through the use of non-ionic surfactants, confers a high stealth in biological medium with reduced non-specific interactions. Tracking individual NEs by fluorescence microscopy techniques would lead to a better understanding of their behavior in cells and thus require the development of bright single particles with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…This dye showed a good molar extinction coefficient of 120 000 m −1 cm −1 (two times higher than Nile Red) and an increased quantum yield of 0.98 (similar to Nile Red). [63] The brightness of DBS fluorophores in oil was enhanced due to higher viscosity, [63] a phenomenon similar to that observed earlier by Texier et al using cyanines. [114] The developed DBS dyes showed highest brightness (quantum yield and molar extinction coefficient) in castor oil (with the highest viscosity) compared with other oils (e.g., MCT and VEA).…”
Section: Brightness Of Dye-loaded Nessupporting
confidence: 72%
See 3 more Smart Citations
“…This dye showed a good molar extinction coefficient of 120 000 m −1 cm −1 (two times higher than Nile Red) and an increased quantum yield of 0.98 (similar to Nile Red). [63] The brightness of DBS fluorophores in oil was enhanced due to higher viscosity, [63] a phenomenon similar to that observed earlier by Texier et al using cyanines. [114] The developed DBS dyes showed highest brightness (quantum yield and molar extinction coefficient) in castor oil (with the highest viscosity) compared with other oils (e.g., MCT and VEA).…”
Section: Brightness Of Dye-loaded Nessupporting
confidence: 72%
“…Recently, a novel dioxaborine dye named DBS-C 8 was developed and encapsulated into NEs with vitamin E acetate as liquid core (around 40 nm) at high concentration of 37 ×10 −3 m in oil without obvious aggregation caused quenching issue and a high quantum yield of 0.44. [63] Moreover, in comparison to NR668, it showed significantly improved photostability and single-particle brightness. These improved optical properties of fluorescent NEs enabled their single-particle tracking as well as determination of their trajectory and velocity in the cytoplasm (Figure 9).…”
Section: Tracking Nanodroplets Inside Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to other types of nano-carriers, NEs have a real advantage to be a liquid reservoir for lipophilic active pharmaceutical ingredients (APIs), and thus, a priori, lipophilic fluorescent probes as models. This original feature has recently allowed the encapsulation of an outstanding number of fluorophores in a single droplet, making ultrabright nano-droplets enabling new possibilities such as single droplet tracking in cells or in small laboratory animals [6][7][8]. Although a large number of literature reports has shown that NE droplets themselves are intrinsically very stable, shown experimentally [9,10], and explained by the fact that droplets cannot enter in contact each other for steric reasons [11][12][13], the important question of the leakage of encapsulated APIs is still not clearly addressed.…”
Section: Introductionmentioning
confidence: 99%